Oxygen consumption and hemodynamics in Type 1 diabetes patients during stress testing - E. I. Sokolov; Yu. I. Demidov; V. A. Dudaev (Российский кардиологический журнал, 2007)
In 128 patients with Type 1 diabetes mellitus (DM-1) and 38 healthy volunteers, hemodynamic component of gas-transporting system was assessed in bicycle stress test, with permanent monitoring of О2 consumption, heart rate (HR), systolic and diastolic blood pressure (SBP, DBP). O2 pulse was calculated, and anaerobic threshold was determined. DM-1 patients were divided into three groups: Group 1 - without clinically manifested microangiopathy; Groups 2 and 3 -with initial and progressed manifestation of late diabetic syndrome. In all three groups, comparing to controls, mean peak О2 consumption and anaerobic threshold were significantly decreased. HR at peak stress was significantly lower inpatients with late diabetic complications than in controls, and О2 pulse was reduced in all three groups. During stress testing, Group 1 demonstrated significant SBP increase, Groups 2 and 3 - significant DBP increase, comparing to respective control levels. In DM-1 patients, disturbances of gas-transporting system hemodynamic component, registered during stress testing, develop before clinical microangiopathy manifestation. The latter progresses substantially during late diabetic syndrome evolution.